Implementation of the Doctrine of the Business Judgment Rule on Bankruptcy Law in Indonesia - Andika Wijaya (Universitas Airlangga, 2019)
One of the mechanisms that can be taken in resolving accounts payable to a limited liability company in bankruptcy. In the case of bankruptcy due to mistakes made personally by the Board of Directors and the Board of Commissioners, they must be responsible for debts held by limited liability companies. The company law regulates the way for the Board of Directors and Board of Commissioners to avoid liability for losses suffered by the company, through the doctrine of the Business Judgment Rule (BJR). In practice, the application of the BJR doctrine in bankruptcy law is characterized by differences in interpretation between law enforcers. Differences in interpretation occur because there is no clear provision in the Republic of Indonesia Law Number 37 of 2004 concerning Bankruptcy and Delay of Obligations to Pay Debt (Law No. 37/2004) which limits the filing of bankruptcy applications to the personal Directors and Board of Commissioners. The research in this article is carried out by reform-oriented research methods, to make changes to Law No. 37/2004 to clarify the application of the BJR doctrine in bankruptcy law in Indonesia. With the implementation of legal reform, it is expected that there will be no difference in interpretation regarding the application of the BJR doctrine to bankruptcy law at the Commercial Court in Indonesia.